Health professional's job satisfaction and its determinants in Ethiopia: a systematic review and meta-analysis - Bekahegn Girma; Jemberu Nigussie; Alemayehu Molla; Moges Mareg (BMC, 2021)
Abstract Background Health professional's job satisfaction is directly related to patient satisfaction and quality of care. Without satisfied health professionals the health system is not functional, and the national and global health related plans are not achieved. However, little is known on the level of health professional's job satisfaction in sub Saharan African countries including Ethiopia. In addition, in Ethiopia there is no summarized evidence helped us an input to design strategies. Therefore, we aimed to assess the pooled prevalence of health professional's job satisfaction and its determinants in Ethiopia. Methods Articles were searched from PubMed, PsycINFO, Hinari, Science Direct, web of science and African journal of online (AJOL) databases, Google and Google scholar. A standardized Microsoft excel spread sheet and STATA software version 16 were used for data extraction and analysis respectively. We followed the Preferred Reporting Items for Systematic reviews and Meta-Analysis to write this report. A random effect meta-analysis model was used to determine the pooled prevalence of job satisfaction. I2 was done to check heterogeneity. Egger's test and funnel plot were conducted to detect publication bias. Subgroup analysis was also conducted. Association was expressed through pooled odd ratio with a 95% CI. Result In this review and meta-analysis, a total of 29 studies were included. The pooled prevalence of health professional's job satisfaction was 46.17% [95% CI (43.08, 49.26)]. The heterogeneity and publication bias test results were I2 = 87.3%, P <  0.001 and Eggers', P = 0.16. Female sex; OR: 2.20 [95% CI (1.63, 2.97)], working environment; OR: 9.50 [95% CI (6.25, 14.44)], opportunity for professional growth and development; OR: 5.53 [95% CI (1.56, 19.56)], staff relationship; OR: 3.89 [95% CI (1.65, 9.17)] and supportive supervision; OR: 5.32 [95% CI (1.77, 15.92)] were associated with health professional's job satisfaction. Conclusion More than half of professionals were dissatisfied with their jobs. Therefore, the ministry of health and stakeholders better to design strategies to increase the level of satisfaction. Furthermore, it is better to strengthen staff relationship and making the working environment more attractive and equipped.